mTOR signaling cascade in psoriatic disease: Double kinase mtor inhibitor a novel therapeutic target - Smriti K Raychaudhuri; Siba R Raychaudhuri (Wolters Kluwer Medknow Publications, 2014)
In this short communication we are providing insight about the regulatory role of the phosphatidylinositol 3-kinase (PI3K)-AKT-mammalian target of rapamycin (mTOR) kinase system in psoriatic disease. This is an upcoming active research field in respect to elucidating the inflammatory and proliferative cascades of psoriatic disease. To provide a new dimension to the understandings of the molecular principles of the pathogenesis of autoimmune diseases, we hypothesized that (i) dysregulation of cytokines and growth factors in autoimmune diseases activate the mTOR signaling system and (ii) the activated mTOR kinase system is a key regulator of the inflammatory/proliferative cascades of the disease process. In support of this hypothesis we have earlier reported that growth factors (nerve growth factor (NGF) and platelet-derived growth factor (PDGF)) and relevant cytokines (interleukin (IL)-17, IL-22) known to be critical for psoriasis, psoriatic arthritis, and rheumatoid arthritis activate the mTOR signaling system. Here, we are providing our latest observations that the mTOR signaling proteins are upregulated in psoriatic skin and further we observed that proliferation of keratinocytes (KC) and synovial cells (synovial fibroblasts (FLS)) of psoriatic arthritis are dependent on the PI3K-AKT-mTOR kinase system. To our knowledge, we are the first to explore whether a double kinase inhibitor of mTOR signal proteins has a therapeutic potential for psoriatic disease. Here we will be sharing our views, our research work in this field and as well we will provide evidences how a double kinase inhibitor of mTOR signal proteins can be an effective therapeutic agent for psoriatic disease.